Lung function and prevalence of respiratory symptoms in Norwegian crab processing workers - Thomassen, Marte Renate; Aasmoe, Lisbeth; Bang, Berit E.; Braaten, Tonje (International Journal of Circumpolar Health, 2017)
Source at http://dx.doi.org/10.1080/22423982.2017.1313513 Background: Seafood processing workers have an increased risk of developing occupational asthma. This has not been studied among Norwegian crab processing workers, nor has the respiratory health of exposed workers been compared to a control group. Objectives: Assessing the impact of working in the crab processing industry on workers ’ respiratory health. Design: A cross-sectional study of the respiratory health in two types of crab processing workers compared to a control group. Methods: The study included 148 king crab ( Paralithodes camtschaticus ) workers, 70 edible crab ( Cancer pagurus ) workers and 215 controls. Workers answered a questionnaire and performed spirometry measurements. χ 2 and Fishers exact tests were performed on self-reported respiratory symptoms. Regression analyses and t-tests were used to assess lung function values. Results: Self-reported respiratory symptoms were higher among crab processing workers com- pared to controls, and higher among king crab workers compared to edible crab workers. There was no significant difference between crab processing workers and controls in lung function measurements. Self-reported doctor-diagnosed asthma prevalence was highest in the control group. Conclusions: Increased respiratory symptoms reported by crab processing workers were not reflected in impaired lung function values or asthma diagnose. We suggest a healthy worker effect among crab processing workers in Norway.